2014
DOI: 10.3390/ijms15022003
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Composition, Molecular Weight Distribution and Gel Electrophoresis of Walnut (Juglans regia L.) Proteins and Protein Fractionations

Abstract: As a by-product of oil production, walnut proteins are considered as an additional source of plant protein for human food. To make full use of the protein resource, a comprehensive understanding of composition and characteristics of walnut proteins are required. Walnut proteins have been fractionated and characterized in this study. Amino acid composition, molecular weight distribution and gel electrophoresis of walnut proteins and protein fractionations were analyzed. The proteins were sequentially separated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 23 publications
2
45
0
4
Order By: Relevance
“…More recently, a study proposed to fractionate and more widely characterize walnut proteins in order to better understand the alleged health inducing contributions of walnut protein additives for use in food (Mao et al 2014). Four extractable protein fractions were obtained according to their solubility (glutenin 72.06%, albumin 7.54%, globulin 15.67%, and prolamin 4.73%).…”
Section: Proteomics Researchmentioning
confidence: 99%
“…More recently, a study proposed to fractionate and more widely characterize walnut proteins in order to better understand the alleged health inducing contributions of walnut protein additives for use in food (Mao et al 2014). Four extractable protein fractions were obtained according to their solubility (glutenin 72.06%, albumin 7.54%, globulin 15.67%, and prolamin 4.73%).…”
Section: Proteomics Researchmentioning
confidence: 99%
“…These results suggest that our pretreatment method was appropriate for a meal to achieve the purpose of this study, although the results did not indicate that it can be applied to all the foods listed in AACT 2015. In the case of amino acid analysis of walnut, which has a high fat content, 10 times as much hexane was added as the sample (15). Thus, the pretreatment method for amino acid analysis will vary depending on the characteristics of each food.…”
Section: Evaluation Of the Validity Of Pretreatment Methods For Amino mentioning
confidence: 99%
“…Mao et al analyzed walnut proteins and classified them into 4 groups as follows: Glutelin (soluble in dilute NaOH), globulin (salt-soluble), albumin (water-soluble) and prolamin (alcohol-soluble), and based on their percentage, most of walnut proteins belong to glutelin group. 47 In another study, it was reported that some peptides resulted from hydrolyzing the walnut proteins have antioxidant activity and could be used as antioxidant components. 48 This fruit also has a lot of free amino acids.…”
Section: Mineral Elementsmentioning
confidence: 99%